2015
DOI: 10.1002/hed.24039
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and efficacy of accelerated radiotherapy with concurrent weekly cisplatin for locally advanced head and neck carcinoma

Abstract: Concomitant weekly cisplatin 40 mg/m(2) with accelerated RT was well tolerated and treatment compliance was high. © 2015 Wiley Periodicals, Inc. Head Neck 38: E559-E565, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In previous studies, the proportions of patients with enteral nutrition dependence varied widely, from 36% to 78% after CCRT and from 38% to 79% after cetuximab‐based RT . The proportion of patients who failed to wean from artificial nutrition has been reported as 22% with both cetuximab‐based RT and CCRT at 30 days after the end of treatment .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, the proportions of patients with enteral nutrition dependence varied widely, from 36% to 78% after CCRT and from 38% to 79% after cetuximab‐based RT . The proportion of patients who failed to wean from artificial nutrition has been reported as 22% with both cetuximab‐based RT and CCRT at 30 days after the end of treatment .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that CCRT increased the risk of enteral nutrition dependence at 6 months compared to cetuximab‐based RT . The proportion of patients receiving the PEG procedure during hospitalization was reported as 50% to 55% in cetuximab‐based RT and 69% to 78% in CCRT . Previous studies reported that enteral nutrition dependence was significantly associated with advanced tumor classification, severe weight loss (>10% from baseline), chemoradiotherapy, and high doses of RT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with postoperative locally advanced head and neck cancer and NPC received cisplatin 100 mg/m 2 every 3 weeks in combination with conventional radiotherapy. Patients who were primarily treated with concomitant chemoradiotherapy received weekly cisplatin 40 mg/m 2 in combination with accelerated radiotherapy . From 2003 until 2006, a 3D‐conformal radiotherapy technique was used.…”
Section: Methodsmentioning
confidence: 99%
“…Although very effective, this treatment is associated with high rates of acute toxicity. An alternative treatment schedule is radiotherapy with weekly cisplatin 40 m/m 2 with good feasibility and efficacy …”
Section: Introductionmentioning
confidence: 99%